Stability investigation of total parenteral nutrition admixture prepared in a hospital pharmacy - Mirković Dušica; Antunović Mirjana; Putić Vesna; Aleksić Dragana (Vojnosanitetski Pregled)
Background/Aim. In the cases when nutrition of patients can not be orally nor enterally performed, parenteral nutrition is a method of the therapy that provides more successful and rapid recovery. In that way, hospitalization can be significantly shorter, healing costs reduced and mortality minimized. Total parenteral nutrition (TPN) admixtures are the most complex systems which contain amino acids, carbohydrates, lipid emulsion, macroelectrolytes (Na+, K+, Ca2+, Mg2+, Cl-, SO42-, PO43-), oligoelements, hydro- and liposoluble vitamines, heparin, insulin and water. Concerning the mentioned complexity, special attention should be payed to physicochemical and microbiological stability of a mixture, because of interactions among components, that can be very hard to analyze. The aim of this study was to investigate the problem of stability of TPN admixtures prepared in a hospital pharmacy. Methods. Admixture TPN was aseptically prepared in laminar air - flow environment on the basis of the specified order in supplementing components and additives to basic solutions. Solutions were kept in sterile multicompartment ethylene-vinyl-acetate bags. After preparation and slow homogenization, TPN admixtures were submitted to physicochemical and microbiological stability analyses in various period of time. The assessment of physical stability of TPN admixture was done on the basis of visual inspection, determination of pH value and measuring of particle size. The investigation of sterility and pyrogenic test were performed according to Ph. Yug. V regulations. Results. Physico-chemical and microbiological analyses were applied and no significant changes in visual sense, pH value and droplet size stability of the TPN admixture were observed during the period of 60 hours. The lipid droplets were smaller in size than 5 μm, that is the most common pharmacopoeia requirement. Conclusion. The results of our study confirmed that a TPN admixture prepared in a hospital pharmacy can be stored without stability loss for at least 60 hours.